“An ad's hidden message": technology-enhanced learning to develop 6th graders' media literacy skills - Iolie Nicolaidou; Ioannou, Yiota (My University, 2014)
Media literacy, defined as students’ “ability to access, analyse, and evaluate messages from different media and also produce messages using different types of media” (Livingstone, 2004) is a very important skill for today’s “digital natives”. Students face difficulties when asked to analyze and critically evaluate multimedia messages (Young, 2012). Similar results are supported by the study “EU Kids Online” (2011), according to which younger children lack basic skills of critical thinking and face difficulties in evaluating or filtering digital content when it comes to the credibility of media. Even though children naturally develop some basic media literacy skills through their interaction with new technologies, the role of formal schooling is crucial for helping students develop these skills (Buckingham, Banaji, Carr, Cranmer & Willet, 2005). This is why countries such as Canada, Australia, the UK, the USA, and France have incorporated media literacy into their curricula (Fedorov, 2003). In Cyprus, this is not the case. Moreover, Cyprus scores among the last countries with regard to the assessment of the level of media literacy country-wide, according to the “Study on Assessment Criteria for Media Literacy Levels” (Celot & Tornero, 2009). Recent calls for research in the area of media literacy have identified the need to search for new designs, teaching approaches, and learning environments that are compatible with contemporary society and students’ interests (Hobbs, 2011). The present study attempts to address this need and focuses on the design, production, implementation and evaluation of a web-based learning environment on media literacy, called: “An ad’s hidden message” that aims to develop 6th graders’ skills in the understanding, analysis and production of advertising messages. The research question that this study seeks to answer is the following: What is the effect of the learning environment “An ad’s hidden message” on the development of 6th graders’ skills in a) understanding and analysing and b) producing advertising messages?. The methodology of the study was a pre-test post-test control group design. Three 6th grade classes of a city school in Cyprus participated in the study. An activity sequence was developed that included a series of activities organized around 12 40-minute lessons to support students in developing media literacy skills in advertising. Two classes, taught by the same researcher, followed this activity sequence. In the first class (intervention class) 23 students interacted with the learning environment, while in the second class 20 students engaged in similar activities that did not involve their engagement with the learning environment (traditional class). A third class of 20 students acted as a control group. A media literacy test, modified from (Hobbs & Frost, 2003) that consisted of 5 closed and 8 open ended questions was administered to all 63 students as a pre-test, before the intervention, and as a post-test upon completion of the intervention. The advertisements that students produced served as additional data for analysis. For triangulation purposes interviews will be conducted with a small number of students. As this is a work-in-progress, the paper will report on and discuss preliminary results of data analysis of student’s performance in media literacy tests. Implications with regard to the effectiveness of the proposed media literacy intervention program will be drawn
Keywords: Media Literacy; Primary School; Blended Learning; 21st Century Skills; Technology-Enhanced Learning